2009
DOI: 10.1016/j.str.2008.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of m7GpppG Binding to Poly(A)-Specific Ribonuclease

Abstract: Poly(A)-specific ribonuclease (PARN) is a homodimeric, processive, and cap-interacting 3' exoribonuclease that efficiently degrades eukaryotic mRNA poly(A) tails. The crystal structure of a C-terminally truncated PARN in complex with m(7)GpppG reveals that, in one subunit, m(7)GpppG binds to a cavity formed by the RRM domain and the nuclease domain, whereas in the other subunit, it binds almost exclusively to the RRM domain. Importantly, our structural and competition data show that the cap-binding site overla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 44 publications
6
57
0
1
Order By: Relevance
“…These surprising results yielded from biophysical and biochemical methods were confirmed by the structures of the PARN RRM complexed with a cap analogue, resolved by multidimensional NMR methods [36] and crystallography [37,38] (Fig. 1d).…”
Section: Accepted M Manuscriptmentioning
confidence: 85%
See 3 more Smart Citations
“…These surprising results yielded from biophysical and biochemical methods were confirmed by the structures of the PARN RRM complexed with a cap analogue, resolved by multidimensional NMR methods [36] and crystallography [37,38] (Fig. 1d).…”
Section: Accepted M Manuscriptmentioning
confidence: 85%
“…Here we have used atomic force microscopy (AFM [39]) in liquid for imaging of immobilized proteins, as well as dynamic light scattering (DLS) measurements and gel filtration experiments in solution to find estimates of the protein shape. We report for the first time the dimensions of the complete PARN molecule, which previously has not been possible to obtain neither by crystallographic studies using truncated versions of PARN [35,38] (Fig. 1) nor from solution studies [40].…”
Section: Accepted M Manuscriptmentioning
confidence: 86%
See 2 more Smart Citations
“…[83][84][85] Biochemical and structural studies revealed that PARN binds to the 7-methylguanosine cap (m 7 G) of mRNAs via specific tryptophan residues. [86][87][88][89] Cap binding enhances the deadenylation activity of PARN. 83,89 PARN is localized to both the nucleus and cytoplasm and is known to play a role in gene expression regulation.…”
Section: Parn Is Essential For Fxr1a-micrornp Mediated Translation Asmentioning
confidence: 99%